Comprehensive genetic testing for primary immunodeficiency disorders in a tertiary hospital: 10-year experience in Auckland, New Zealand. Issue 1 (December 2016) - Woon, See-Tarn; Ameratunga, Rohan
Abstract Background and purpose New Zealand is a developed geographically isolated country in the South Pacific with a population of 4.4 million. Genetic diagnosis is the standard of care for most patients with primary immunodeficiency disorders (PIDs). Methods Since 2005, we have offered a comprehensive genetic testing service for PIDs and other immune-related disorders with a published sequence. Here we present results for this program, over the first decade, between 2005 and 2014. Results We undertook testing in 228 index cases and 32 carriers during this time. The three most common test requests were for X-linked lymphoproliferative (XLP), tumour necrosis factor receptor associated periodic syndrome (TRAPS) and haemophagocytic lymphohistiocytosis (HLH). Of the 32 suspected XLP cases, positive diagnoses were established in only 2 patients. In contrast, genetic defects in 8 of 11 patients with suspected X-linked agammaglobulinemia (XLA) were confirmed. Most XLA patients were initially identified from absence of B cells. Overall, positive diagnoses were made in about 23% of all tests requested. The diagnostic rate was lowest for several conditions with locus heterogeneity. Conclusions Thorough clinical characterisation of patients can assist in prioritising which genes should be tested. The clinician-driven customised comprehensive genetic service has worked effectively for New Zealand. Next generation sequencing will play an increasing role in disorders with locus heterogeneity.